Clinical efficacy of percutaneous intramedullary aspiration, irrigation, and injection of absorbable bone in pediatric simple bone cyst - Xu, Gang; Sun, Wei; Zhang, Shiquan; Li, Wei (Frontiers in Pediatrics, 2025)
BackgroundSimple bone cysts (SBCs) are common benign bone lesions that primarily affect the long bones of children and adolescents. Due to their tendency to recur and their potential to cause pathological fractures, a range of treatment strategies has been investigated. This study evaluates the clinical efficacy of percutaneous intramedullary aspiration, irrigation, and injection of absorbable bone (PAIB) in the treatment of pediatric SBCs.MethodsAll patients underwent the PAIB procedure. Postoperative evaluation involved radiographic assessment to monitor recurrence and identify potential complications, with magnetic resonance imaging (MRI) performed when clinically indicated.ResultsIn this cohort of 36 patients with SBC treated using the PAIB technique, the mean follow-up duration was 33.5 months (range: 12–66 months). Recurrence occurred in 6 patients (16.6%), including one case complicated by a pathological fracture. Five of the recurrent cases underwent repeat PAIB procedures, resulting in complete resolution in two patients. Postoperative imaging revealed small residual cysts in three cases. Bone healing was successfully achieved in 32 patients. Graft bone exudation, identified as a potential risk factor for recurrence, was observed in seven patients. All patients exhibited satisfactory functional outcomes throughout the follow-up period.ConclusionPAIB appears to be a safe, effective, and minimally invasive treatment option for the management of pediatric simple bone cysts.